Effect of foliar spray with GA3 and CCC on morpho-physiological parameters of okra (Abelmoschus esculentus L.) - بوارس, متيادي; صهيوني, فهد; خرماشو, ديما (Latakia University Journal -Biological Sciences Series, 2022)
The aim of the research was to study the effect of foliarspray okra (Abelmoschus esculentus L.) with different concentrations of gibberellin acid (GA3) (25,50,75,100 ppm) and cycocil (CCC) (400,600,800,1000 ppm) on morphological and physiological growth indicators. The experiment was effectuated in the village of Al-Dabaika of Al-Mazira'a district, using okra (local) variety, with three replications and fifteen plants for each replicate, based on complete randomised design, and the results were analyzed statistically using the Genstat-12 statistical analysis progra The results showed that GA3 at 75 ppm was effective and gave the best plant height (206.9 cm), leaf area (16960.9 cm2 / plant) and L.A index (5.5), compared to control. CCC had an effective role in increasing the number of lateral branches on the main stem and the total number of leaves. The highest values were recorded when treating with of 600 ppm of CCC, as (5 branches / plant) and (90.6 leaves / plant. The result showed as well, that leaves content of total chlorophyll and chlorophyll a increased when treated with CCC at 600 ppm, while the amount of total chlorophyll was (6.23 mg / g freshweight) and chlorophyll a (4.71 mg / g weight), which was positively reflected in the increase the Net Assimilation Rate (0.0113 g / cm2 / day), Treatment with these regulators increased the relative growth rate which was resulted from the increase in plant dry weight, and recorded (2.68 mg / g / day) when spraying with GA3 75 ppm and (2.11 mg / g / day) when sprayed with CCC at 600 ppm.